Contribution of agricultural exports to economic growth in Pakistan - Muhammad Zahir Faridi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The main objective of the present analysis is to explore and quantify the contribution of agricultural exports to economic growth in Pakistan. We have estimated the relationship between Gross domestic product (GDP) and agricultural and non agricultural exports for Pakistan employing Johansen co-integration technique for the period 1972 - 2008. The findings of the study show that the agricultural exports have negative and significant effect on economic growth while agricultural exports elasticity is 0.58. Moreover there is bidirectional causality in agricultural exports and real GDP. It is suggested that non agricultural exports should be promoted.
Keywords: 330; Pakistan; Agricultural exports; non agricultural exports; Johansen cointegration; labor force; Agraraußenhandel; Wirtschaftswachstum; Kointegration; Schätzung; Pakistan